Introduction: The Inaugural John Dugard Lecture in International Law, University of Johannesburg, 25 October 2018 - Strydom, Hennie A (South African Yearbook of International Law, 2020)
The inaugural John Dugard Lecture in International Law, University of Johannesburg, 25 October 2018 In 2015, a steering committee made up of myself and other members of the South African Branch of the International Law Association (ILA) commenced our planning for hosting the 77th Biennial Conference of the ILA, which was to take place in Sandton in August 2016, two years after our hosting bid was approved by the Executive Committee of the ILA in London.